2019
DOI: 10.1039/c9cp04719k
|View full text |Cite
|
Sign up to set email alerts
|

β12-Borophene becomes a semiconductor and semimetal via a perpendicular electric field and dilute charged impurity

Abstract: In this paper, the possible electronic phase transitions of β12-borophene crystal are examined using a five-band tight-binding calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Researchers observed the Dirac fermions in b 12 -borophene by angle-resolved photoemission spectroscopy, a tight-binding model and rstprinciples calculations. [11][12][13][14] The results indicated that b 12 is particularly metallic. [15][16][17][18][19] It is understood that lattice thermal conductance in the ballistic regime of borophene is very high and similar to graphene in low frequencies, phonons transition in borophene is almost isotropic, and for high frequencies, phonon transition is one-dimensional, and phonons move in one direction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Researchers observed the Dirac fermions in b 12 -borophene by angle-resolved photoemission spectroscopy, a tight-binding model and rstprinciples calculations. [11][12][13][14] The results indicated that b 12 is particularly metallic. [15][16][17][18][19] It is understood that lattice thermal conductance in the ballistic regime of borophene is very high and similar to graphene in low frequencies, phonons transition in borophene is almost isotropic, and for high frequencies, phonon transition is one-dimensional, and phonons move in one direction.…”
Section: Introductionmentioning
confidence: 96%
“…However, researchers are trying to overcome this by using an appropriate substrate, but the difference between lattice parameters of the substrate and two-dimensional material can make it unstable. 10 Borophene, due to its electron mobility, band gap, and anisotropic properties and having both a massless Dirac fermion and massless/massive triplet fermions 11,12 is different from other 2D materials. Researchers observed the Dirac fermions in b 12 -borophene by angle-resolved photoemission spectroscopy, a tight-binding model and rstprinciples calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the average over the random local conguration of many impurities, we neglect the importance of the location of impurity in the present formulation. [57][58][59] Thus, the impurity potential U ¼ n iÎ contains the non-zero elements inÎ meaning that the impurity resides on the whole AA-stacked layers. The sign of n i affects the scattering process, such that the positive scattering potential n i binds up the negative electrons or positive holes, while negative n i attracts positive electrons.…”
Section: Impurity Scattering Effectsmentioning
confidence: 99%
“…Beside the fundamental characteristics of topological states mentioned above, many novel physics properties have also been explored in topological insulators, topological Weyl/Dirac semimetals by breaking down the crystal symmetry [23], considering anisotropic and noncollinear interactions including Dzyaloashinsky-Moriya (DM) interaction, strong Rashba spini-orbit interaction and Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction [24][25][26]. In the works by Yarmohammadi et al, the magnetic phase transition and the enhancment of thermoelectric power factor have been proposed in the topological crystalline insulator SnTe associated with four Dirac cones by doping magnetic impurities or by changing external perturbation, respectively [24,25].…”
Section: Introductionmentioning
confidence: 99%